The Study of Chemical and Organoleptic PropertiesTofu Nugget on Various Percentage In Additionto The Seaweed Porridge (Eucheuma cottoni): The Study of Chemical and Organoleptic Properties Tofu Nugget on Various Percentage In Addition to The Seaweed Porridge (Eucheuma cottoni - Nurul Asriani; Nurhayati .; Yeni Sulastri (Pro Food, 2021)
ABSTRACT Nugget is a form/kind of processed meat product made from ground meat with mold foursquare pieces and coated with seasoned flour. This study aims to determine seaweed porridge's effect on the chemical and organoleptic properties of tofu nuggets. The method used in this study was an experimental method by conducting experiments in the Laboratory. The design that used in this study was a Completely Randomized Design (CRD) with one factor treatment, namely the addition of seaweed pulp with 6 treatments in making tofu nuggets, namely P0 = 0% seaweed pulp (as a control), P1 = 10%, P2 = 20 %, P3 = 30%, P4 = 40%, P5 = 50%. The result of the Data from observational analysis using diversity analysis at a 5% significance level. If there is a significantly different treatment, further tests (BNJ) are carried out at the same real level. The study results show that the concentration of the addition of seaweed porridge significantly influences the chemical properties (water content and ash content) and organoleptic properties (color and taste) while for protein content, texture and aroma did not significantly affect. The best treatment was obtained at P5 treatment with water content (54.33%), ash content (6.53%), protein content (5.94%) with savoty taste, brown color, soft texture, and preferred aroma. ABSTRAK Nugget adalah suatu bentuk produk olahan daging yang terbuat dari daging giling yang dicetak dalam bentuk potongan empat persegi dan dilapisi dengan tepung berbumbu. Penelitian ini bertujuan untu mengetahui pengaruh penambahan bubur rumput laut terhadap sifat kimia dan organoleptik nugget tahu. Metode yang digunakan dalam penelitian ini adalah metode eksperimental dengan melakukan percobaan di Laboratorium. Rancangan yang digunakan dalam penelitian ini adalah Rancangan Acak Lengkap (RAL) dengan perlakuan satu faktor yaitu penambahan bubur rumput laut dengan 6 perlakuan dalam pembuatan nugget tahu yaitu P0 = 0 % bubur rumput laut (sebagai control) , P1 = 10 %, P2 = 20 %, P3 = 30 %, P4 = 40 %, P5 = 50 %. Data hasil pengamatan analisa menggunakan analisa keragaman pada taraf nyata 5%. Bila ada perlakuan yang berbeda nyata maka dilakukan uji lanjut (BNJ) pada taraf nyata yang sama. Hasil penelitian menunjukan bahwa konsentrasi penambahan bubur rumput laut berpengaruh secara nyata terhadap sfat kimia (kadar air dan kadar abu) serta sifat organoleptik (warna dan rasa) sedangkan untuk kadar protein, tekstur dan aroma tidak berpengaruh secara nyata. Perlakuan terbaik diperoleh pada perlakuan P5 dengan kadar air (54,33%), kadar abu (6,53%), kadar protein (5,94%) dengan rasa gurih, warna coklat, tekstur lembut dan aroma yang disukai.